Review on Big Data Security in Hadoop (International Journal of Engineering and Computer Science, 2014)
These instructions provide you guidelines for preparing papers for International Journal of engineering & computer science Hadoop popularly used for processing large amount of data on its distributed programming framework with Hadoop distributed file system (HDFS), but processing sensitive or personal data on distributed environment demands secure computing. Originally Hodoop was invented without any security model. The encryption and decryption are used before writing and reading data from Hadoop distributed file system (HDFS) respectively. Advanced Encryption Standard (AES) enables protection to data at each cluster, it perform encryption/decryption before read/write respectively. Hodoop running on distributed environment, it uses commodity hardware which is a network model require a strong security mechanism, in addition kerberos used for authentication it offers access control list and audit mechanisms, to ensure the data stored in the Hadoop file system is secure.